II. Dr. Machlup's Commonsense of the Elasticity of Substitution - Robinson, Joan (Review of Economic Studies, 1936)
Journal Article Further Notes on Elasticity of Substitution: II. Dr. Machlup's Commonsense of the Elasticity of Substitution Get access Joan Robinson Joan Robinson Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 2, February 1936, Pages 148–150, https://doi.org/10.2307/2967507 Published: 01 February 1936